TITIK TITIK TITIK - Moch. Gigin Ginanjar (Saraswati)
Titik Titik Titik is a piece of music that inspired by “Three”. Consisting of “Three” number, “Three” pattern and triangle which found in daily life easily. Birth, life and death, the “Three” pattern, is a main theme of the composition. The meaning of Titik Titik Titik itself is an odyssey of life to reach the aim by stepping from a point to another point and then reach the last one.Composer had been through many creative process steps. Starting from exploration, improvisation, composing and then end with a performance. As the title itself, this piece of music consist of three parts. Its tempo and dynamics will trick the audience’s feeling. Titik Titik Titik tries to review the old discourse about gamelan which gets contemporary treatment without losing traditional patterns & forms and also the aesthetic values of gamelan itself. Nothing is change from gamelan, it is just need the new treatment by considering this era. Gamelan is a spirit, not an object, while the gamelan instrument is just a medium.